Phytoplankton as New Taxa and Report for Bangladesh - Bhuiyan, M A H; Mohid, M; Choytee, S N; Islam, M R; Rahaman, A; Nahin, M; Khondker, M (Journal of Biodiversity Conservation and Bioresource Management, 2024)
In the present paper, a total of 12 species of phytoplankton have been described of which one new variety (Pediastrum duplex var. reniformae var. nov.) and one new forma (Pediastrum duplex var. gracillimum fa. rotatus fa. nov.) from the phytoplankton have been described as new to science. The other 10 species of phytoplanktons have been described as new report from Bangladesh. The systematic account for each of the above-mentioned species and their taxonomic position and photomicrographs are elaborated. Biodivers. Conserv. Bioresour. Manag. 2024, 10(1): 91-98